Paper 85: Superficial MCL Augmented Repair Versus Reconstruction: A Multi-Center Randomized Controlled Trial. Issue 7 (30th July 2022) - LaPrade, Robert; Dornan, Grant; Kennedy, Mitchell; Cram, Tyler; Dekker, Travis; Strauss, Marc; Engebretsen, Lars; Lind, Martin; DePhillipo, Nicholas
Objectives: The purpose of this study was to compare clinical outcomes between randomized groups who underwent MCL augmentation repair versus MCL autograft reconstruction. Methods: Patients were prospectively enrolled from 2013 to 2019 from 3 centers (United States, Norway, Denmark). Grade III superficial (sMCL) injuries were confirmed by stress radiography. Patients were randomized to an anatomic sMCL reconstruction versus an augmented repair with surgical treatment determined after examination under anesthesia confirmed sMCL incompetence. Post-operative visits occurred at 6 weeks and 6 months for repeat evaluation and repeat stress radiography at final follow-up. Patient reported outcome measures (PROMs) were obtained preoperatively and postoperatively at 6 months, 1 year, and at final follow-up. The two one-sided t-test (TOST) procedure was used to test clinical equivalence for side-to-side difference in valgus gapping, and Mann-Whitney U-test was used to compare postoperative PROMs between groups. Results: Fifty-four patients were prospectively enrolled from 3 centers. The average overall patient age was 38.0 years (standard deviation (SD = 14.2 years), average body mass index was 25.0 (SD = 3.6). Preoperative valgus stress radiographs demonstrated 3.74 mm (SD = 1.1 mm) of increased side-to-side gapping overall, while it was 4.10 mm (SD = 1.46 mm) in the MCL augmentation group and 3.42 mm (SD = 0.55) in the MCL reconstruction group (p = 0.036). Postoperative valgus stress radiographs at an average of 6 months were 0.21 mm (SD = 0.81 mm) for MCL augmentation and 0.19 mm (SD = 0.67 mm) for MCL reconstruction (p = 0.940). At final follow-up (minimum 1-year), Lysholm scores were significantly higher in the reconstruction group (median 90, inter-quartile range 83–99) compared to the repair group (median 80, IQR 67-92; p=0.031). Final IKDC scores were significantly higher for the reconstruction group (median 85, IQR 68-89) compared to the repair group (median 72, IQR 60-78; p=0.039). Postoperative Tegner scores were not significantly different between the repair group (median 5, IQR 3.5-6) and the reconstruction group (median 5.5, IQR 4-7; p=0.123). Patient satisfaction was not significantly different between the repair (median 7.5, IQR 5.75–9.25) and reconstruction groups (median 9, IQR 7 - 10; p=0.184). There were no reported cases of DVT, infection, or arthrofibrosis in any patient in either group. There were no reported MCL graft ruptures in either the augmentation or reconstruction group as indicated from valgus stress radiographs (≥ 3.2 mm) and physical examination at 12 months postoperatively. Conclusions: There was no difference in objective outcomes between a sMCL augmentation repair versus a complete sMCL reconstruction at one year postoperatively. Patient reported clinical outcomes favored the reconstruction over repair. This randomized controlled trial demonstrated that anatomic-based treatment of MCL tears with an early knee motion program had low risk of graft attenuation and complications. Table 1. Comparison of baseline covariates between MCL Treatment Groups. † Table A2. Comparison of baseline covariates between sites. †